Advancing restrictive deterrence: A qualitative meta-synthesis. (September 2016) - Moeller, Kim; Copes, Heith; Hochstetler, Andy
Abstract: Purpose: Restrictive deterrence refers to the strategies offenders use to reduce their risk in response to sanctions. It occurs when offenders reduce the frequency, severity, or duration of their offending, or displace their crimes temporally, spatially, or tactically. We summarize and synthesize qualitative research focused on restrictive deterrence. Methods: We conduct a qualitative meta-synthesis (QMS) on research on restrictive deterrence with the aims of integrating, comparing, and translating findings across 17 studies. The studies examine restrictive deterrence in drug dealing, prostitution and auto-theft. The method reveals coherent themes and provides interpretations spanning the works to guide further investigation. Results: Offenders use strategies for avoidance and management of arrest risk and mitigation of punishment in response to sanction threats. Their advance plans and mental preparations structure crime choices. However, both their decisions and their strategies are subject to many influences including variable frictions, restricted options, and bounded rationality. Conclusions: Reductions in offending from deterrent efforts, including the frequency, duration and severity of crime is crime-contingent and partially offset by offenders becoming more embedded in criminal networks and emboldened as they perceive their adaptations as effective. Highlights: Elaborates on restrictive deterrence using qualitative meta-synthesis Restrictive deterrence should emphasize change in behavior. Particularistic strategies include avoidance, management, and mitigation. Strategies are designed to avoid detection and reduce potential sanctions. Restrictive deterrence is a realistic framework for examining sanction effects.